1994
DOI: 10.1046/j.1471-4159.1994.63062172.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain ATP Depletion Induced by Acute Ammonia Intoxication in Rats Is Mediated by Activation of the NMDA Receptor and Na+, K+‐ATPase

Abstract: Injection of large doses of ammonia into rats leads to depletion of brain ATP. However, the molecular mechanism leading to ATP depletion is not clear. The aim of the present work was to assess whether ammoniuminduced depletion of ATP is mediated by activation of the NMDA receptor . It is shown that injection of MK-801, an antagonist of the NMDA receptor, prevented ammoniainduced ATP depletion but did not prevent changes in glutamine, glutamate, glycogen, glucose, and ketone bodies . Ammonia injection increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 172 publications
(83 citation statements)
references
References 26 publications
(37 reference statements)
4
77
2
Order By: Relevance
“…Typically, these ammonia levels are not nearly as elevated as those that have been observed in some conditions that can cause autism, such as urea cycle disorders [66] . Ammonia requires three ATP molecules to be converted into urea and in animal studies, elevated ammonia can lead to brain ATP depletion [67] . Therefore, the increased ammonia noted in autism may be both consequentially and causally related to ATP depletion.…”
Section: Biomarkers Of Classical Mitochondrial Disease and Mtd In Autmentioning
confidence: 99%
“…Typically, these ammonia levels are not nearly as elevated as those that have been observed in some conditions that can cause autism, such as urea cycle disorders [66] . Ammonia requires three ATP molecules to be converted into urea and in animal studies, elevated ammonia can lead to brain ATP depletion [67] . Therefore, the increased ammonia noted in autism may be both consequentially and causally related to ATP depletion.…”
Section: Biomarkers Of Classical Mitochondrial Disease and Mtd In Autmentioning
confidence: 99%
“…So ammonia level in blood increases 9 . Increased ammonia level in autism spetrum disorder children may lead to toxicity and ATP depletion in brain 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The toxic effect of ammonia on the brain is mediated by activation of NMDA receptors [5,6]. This receptor has a calcium channel that is permeable only for extracellular Ca 2+ and K + and for intracellular Na + .…”
Section: Calcium Increases Brain Mitochondrial Mao-a Activity In Vitromentioning
confidence: 99%
“…Excitotoxicity is regarded as a potential mechanism of cell death in acute and chronic neurological diseases as well as under conditions associated with hyperammonemia. It has been shown that acute intoxication with large doses of ammonia result in activation of NMDA receptors in rat brain [5,6]. The mechanisms by which overactivation of NMDA receptors lead to neuronal degeneration and death involve the increase in Ca 2+ concentration in the postsynaptic neuron [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation